2016
DOI: 10.1108/jsma-11-2014-0092
|View full text |Cite
|
Sign up to set email alerts
|

Organizational slack in declining firms and surviving firms

Abstract: Purpose – There is a preponderance of evidence in the established literature that declining firms have lower levels of organizational slack when compared with surviving firms. To further advance the current literature, the purpose of this paper is to examine whether or not organizational slack in its various forms differ in declining firms and in surviving firms. Additionally, this study examines whether there is a change in the extent of slack in the declining firms in the years immediately pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 58 publications
0
14
0
1
Order By: Relevance
“…This adaptive ability is frequently linked to the concept of organizational slack, defined as “the pool of resources in an organization that is in excess of the minimum necessary to produce a given level of organizational output” (Nohria and Gulati, 1997, p. 32). Moreover, prior studies have found evidence of less organizational slack in declining firms that went bankrupt that in surviving firms (Guha, 2016; Singh, 1986).…”
Section: Analysis Of Resultsmentioning
confidence: 98%
“…This adaptive ability is frequently linked to the concept of organizational slack, defined as “the pool of resources in an organization that is in excess of the minimum necessary to produce a given level of organizational output” (Nohria and Gulati, 1997, p. 32). Moreover, prior studies have found evidence of less organizational slack in declining firms that went bankrupt that in surviving firms (Guha, 2016; Singh, 1986).…”
Section: Analysis Of Resultsmentioning
confidence: 98%
“…Mishina et al (2004) reported that when firms pursued growth through product expansion, financial slack was positively related to firms’ short-term growth, whereas human resources slack negatively moderated this relationship. Results of other empirical studies also showed that slack with different levels of managerial discretion produced different roles on performance (Marlin and Geiger, 2015; Mousa et al , 2013; Xu et al , 2015; Guha, 2016). Moreover, Paeleman and Vanacker’s study (2015) suggested that neither too much discretion over resources (managers have discretion over both financial and human resources) nor too limited discretion over resources (managers have constraints on both financial and human resources) are optimal for firm performance and survival.…”
Section: Literature Reviewmentioning
confidence: 83%
“…All over-financed SMEs were instructed by the regulatory authority to use the over-financed capital raised through IPO in their main business areas and to report the usage in their annual reports. In fact, recent studies have reported that slack with different levels of managerial discretion produced divergent role on performance (Marlin and Geiger, 2015; Mousa et al , 2013; Guha, 2016). Unabsorbed slack (higher discretion) was found positively contribute to firms’ product innovation (Liu et al , 2012) and corporate social performance (Xu et al , 2015), whereas absorbed slack (lower discretion) had either lower positive or negative effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Algumas empresas conseguem se reorganizar com sucesso durante o declínio e continuar a atuar (Guha, 2016) e essa é outra perspectiva de estudo do tema sucesso e fracasso, a recuperação organizacional (turnaround) e as estratégias usadas para melhorar o desempenho da empresa em uma ampla gama de condições (Josefy et al, 2017). Pajunen (2005) afirma que o declínio é a primeira etapa de um processo de recuperação.…”
Section: Referencial Teóricounclassified